RIPPLE EFFECTS OF IMPLEMENTING EVIDENCE‐BASED MENTAL HEALTH INTERVENTIONS IN A COMMUNITY‐BASED SOCIAL SERVICE ORGANIZATION. Issue 8 (November 2016) - Beehler, Sarah
Abstract : Concerns over the quality of mental health services in the United States have led to the creation, dissemination, and implementation of evidence‐based mental health interventions (EBMHIs). Though it is widely acknowledged that interventions have ripple effects, the effects of these interventions on the systems in which they are implemented (i.e., practice settings) are unclear. The purpose of this qualitative pilot study was to explore both practitioner‐ and organization‐level ripple effects of EBMHIs implemented in a community‐based agency. We identified 4 categories of effects on practitioners (work roles and responsibilities, knowledge, thoughts and feelings, and behavior and communication) and 2 categories of effects on the organization (structure, programming). Findings suggest that it is possible to identify ripple effects through qualitative interviews. Implications for future research on mental health intervention effects are discussed.